Green synthesis of silver nanoparticles of boswellic acid and it’s in vitro anticancer activity - SNEHA THAKUR; Dr. G. KRISHNA MOHAN (International Journal of Pharma and Bio Sciences, 2019)
Newer anticancer agents are always in current trend of research and should be developed either to activate the extrinsic pathway (death receptor mediated) or intrinsic pathway (mitochondria dependent – Apoptosis pathway). Boswellic acid is a pentacyclic triterpene with high retention and low solubility, also Boswellic acid is recommended along with a fatty meal to increase the absorption. To overcome these limitations, nanoparticular formulations may be synthesized .The green synthesis method is cost effective and eco friendly process used to derive phytochemicals with modulated pharmacodynamics and pharmacokinetic parameters. Silver nanoparticles have good physicochemical properties like high dispersion, high surface area and smaller size with wide therapeutic properties. The main objective of this work is to synthesize boswellic acid silver nanoparticles and to investigate it’s in vitro anticancer potential. Boswellic acid was isolated, purified from the gum resin of the plant Boswellia serrata by column chromatography, later silver nanoparticles of the boswellic acid were synthesized and characterized further by UV-Vis spectral studies, FTIR, XRD, SEM and DLS studies. The synthesized nanoparticles were 21.5±0.5 nm measured by DLA studies without signs of agglomeration and were found to have hexagonal cubic structure based on SEM and XRD measurements. .Furthermore the synthesized boswellic acid silver nanoparticles were screened for in vitro anticancer activity against human skin cancer cells line G361 using ADR (doxorubicin) as reference standard. The synthesized boswellic acid Nanoparticles exhibited anticancer activity nearer to the standard ADR. The future perspectives may be oriented in finding invivo pharmacological screening and also assessing the pharmacodynamics and pharmacokinetic parameters.